INTEGRATION OF ISLAMIC IDENTITY-MODERNITY: THE ROLE OF FASHION AND BRAND ON STUDENT HALAL LIFESTYLE - Amir Salim; Reni Hariani; Ambrina Rosada (I-Finance Journal, 2025)
This study highlights the phenomenon of integrating Islamic identity and modernity among the younger generation. This research aims to analyze the influence of fashion trends and brand image in shaping students' halal lifestyle from an Islamic perspective. This study employs a quantitative approach involving a population of 203 students and a sample of 67 respondents. Data analysis techniques include validity and reliability tests, classical assumption tests, multiple linear regression, and hypothesis testing (t-test and F-test). The results indicate that simultaneously, fashion trends and brand image significantly influence the halal lifestyle of female students at the Faculty of Islamic Economics, Universitas Indo Global Mandiri, as evidenced by the calculated F-value (201.068), which is greater than the F-table value (3.985). In conclusion, this study confirms that students are able to integrate values of modernity through brand consumption and fashion trends without abandoning their Islamic identity. This indicates that the halal fashion industry plays a strategic role in facilitating religious expression within the context of a modern lifestyle